2021
DOI: 10.1038/s41598-021-95020-8
|View full text |Cite
|
Sign up to set email alerts
|

Mueller matrix imaging for collagen scoring in mice model of pregnancy

Abstract: Preterm birth risk is associated with early softening of the uterine cervix in pregnancy due to the accelerated remodeling of collagen extracellular matrix. Studies of mice model of pregnancy were performed with an imaging Mueller polarimeter at different time points of pregnancy to find polarimetric parameters for collagen scoring. Mueller matrix images of the unstained sections of mice uterine cervices were taken at day 6 and day 18 of 19-days gestation period and at different spatial locations through the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 54 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Recently, Lee et al. 34 demonstrated that the images of polarization and depolarization parameters with LMMD are available for collagen visualization of cervical tissues using a liquid crystal-based Mueller polarimetric imaging system. The results for the mice model of pregnancy indicated that this method has a good potential to become a clinical tool for in vivo detection of the PTB risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lee et al. 34 demonstrated that the images of polarization and depolarization parameters with LMMD are available for collagen visualization of cervical tissues using a liquid crystal-based Mueller polarimetric imaging system. The results for the mice model of pregnancy indicated that this method has a good potential to become a clinical tool for in vivo detection of the PTB risk.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Li et al 33 used Mueller matrix microscopy data, 32 the logarithmic decomposition approach, and polarized Monte Carlo (MC) modeling for analyzing tissue microstructure in human skin equivalents. Recently, Lee et al 34 demonstrated that the images of polarization and depolarization parameters with LMMD are available for collagen visualization of cervical tissues using a liquid crystal-based Mueller polarimetric imaging system. The results for the mice model of pregnancy indicated that this method has a good potential to become a clinical tool for in vivo detection of the PTB risk.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown earlier that tissue polarimetry techniques could be effectively combined to juxtapose polarization and depolarization parameters from different health conditions after scanning, embrace the Poincaré sphere visualization for qualitative differentiation, and construct various depolarization spaces [20][21][22][23][24][25][26][27][28]. Ample diagnostic information related to the morphology of the tissue specimens under study is encoded in their Mueller matrices [26,[29][30][31][32]. Nevertheless, the intertwined relation between the samples' polarization and depolarization properties and their matrix elements is accessible only after the application of pertinent decomposition algorithms [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al. 15 showed that Mueller matrix imaging polarimetry (MMIP) is an effective technique for performing the rapid and precise scoring of collagen in pregnancy to evaluate the preterm birth risk. Liu et al.…”
Section: Introductionmentioning
confidence: 99%